Phraseological units in the Pons Wörterbuch für Schule und Studium - Robles i Sabater, Ferrán (Revista de Filología Alemana, 2011)
Until very recently, phraseology has not occupied its rightful place in linguistics despite the frequent appearance of the units it deals with and their importance for everyday language. From the 90s onwards, there has been growing interest in studies on phraseological units (PUs) and the number of publications dealing with description, comparison and analysis of the subject has multiplied. Despite this, there are still a number of areas of phraseology that linguistics has hardly addressed. One such area is the treatment afforded to PUs by monolingual and bilingual dictionaries. Our aim is to put forward a view of the way that one of most commonly used dictionaries for Hispanic German language students, the Pons Wörterbuch für Schule und Studium (2003) by E. Böhle/J. Ràfols/E. Schellert, describes, analyses and presents PUs.